2007
DOI: 10.1007/s10439-007-9288-8
|View full text |Cite
|
Sign up to set email alerts
|

Flow and High Affinity Binding Affect the Elastic Modulus of the Nucleus, Cell Body and the Stress Fibers of Endothelial Cells

Abstract: Cell mechanical properties are important in the adhesion of endothelial cells to synthetic vascular grafts exposed to shear flow. We hypothesized that the local apparent elastic modulus of the nucleus and the cell body would increase to a greater extent for cells adherent via the dual ligand (integrin-fibronectin/avidin-biotin) and exposed to flow, than for cells treated with either ligand alone. High affinity avidin-biotin bonds and in vitro flow exposure were used to improve adhesion to grafts thereby alteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 29 publications
3
18
0
Order By: Relevance
“…6), though cell mechanics data for mesenchymal stem cells derived from bone marrow and seeded on glass and polystyrene substrates have been reported previously by others [43]. ASCs attached to SFCS were relatively stiffer than ASCs attached to glass and other cell types examined previously [35,44]. Prior AFM studies reveal that the increase in apparent elastic modulus of cells is directly correlated with an increase in stress fiber density, due to the AFM probe sensing the stress fibers over the apical surface as it indents the surface in order to obtain the force-indentation curves [35,44].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…6), though cell mechanics data for mesenchymal stem cells derived from bone marrow and seeded on glass and polystyrene substrates have been reported previously by others [43]. ASCs attached to SFCS were relatively stiffer than ASCs attached to glass and other cell types examined previously [35,44]. Prior AFM studies reveal that the increase in apparent elastic modulus of cells is directly correlated with an increase in stress fiber density, due to the AFM probe sensing the stress fibers over the apical surface as it indents the surface in order to obtain the force-indentation curves [35,44].…”
Section: Discussionmentioning
confidence: 75%
“…ASCs attached to SFCS were relatively stiffer than ASCs attached to glass and other cell types examined previously [35,44]. Prior AFM studies reveal that the increase in apparent elastic modulus of cells is directly correlated with an increase in stress fiber density, due to the AFM probe sensing the stress fibers over the apical surface as it indents the surface in order to obtain the force-indentation curves [35,44]. In this study, F-actin stress fiber density was examined for ASCs adherent to SFCS and glass surfaces and was found to be significantly higher for ASCs adherent to SFCS than to a glass surface (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Inlet flow was prescribed to give a centerline velocity of 1 mm/s, and outlet pressures were set at 0 pascals (Pa) to match experimental conditions. The Young's moduli of the endothelial cytoplasm and nuclei (Ecytoplasm = 8.2 kPa, Enucleus = 15.1 kPa) were used to define nearly incompressible neo-Hookean material descriptions (Kcytoplasm =137 kPa, Ccytoplasm = 1.37 kPa; Knucleus = 252 kPa, Cnucleus = 2.52 kPa) capable of large deformation (54), while the PDMS channel was assigned a Young's modulus of 500 kPa (55). Whole blood was a assigned a viscosity of 2.7 cP, a value experimentally reported for blood at the relevant shear stress in a tube with a diameter of 20-30 μm (56).…”
Section: Methodsmentioning
confidence: 99%
“…138 Atomic force microscopy has also been used to investigate the elastic modulus of nuclei in whole cells and similarly found that nuclei in sheared cells are stiffer than control nuclei. 139 However, the molecular mechanism for this shearinduced stiffening of nuclear structure that persists after nuclear isolation remains unclear.…”
Section: How Does Force Affect the Nucleus?mentioning
confidence: 99%
“…The shape and mechanics of the nucleus is known to adapt and reorder when cells are exposed to force. 138,139 However, it remains unclear how the genes within the nucleus are subsequently reordered or if pockets of heterochromatin are altered by force or by lamin reorganization. Lamins are not only found at the nuclear periphery but also form intranuclear structures and can modulate chromatin organization.…”
Section: Searching For Evidence: Can Forces On the Nucleus Directly Mmentioning
confidence: 99%